SOBREVIVÊNCIA DE CERATOCYSTIS FIMBRIATA EM SOLO DE PORMAR DE MANGUEIRA - SOUZA, Eli Domingos de Oliveira; MENDONÇA, Cristiane Gonçalves; GRAICHEN, Felipe André Sganzerla; ROSA, Caike Figueredo Fernandes; CAVALCANTI, Vittor Gomes; SANTOS, Stephany dos (ANAIS DO ENIC, 2018)
-